2015
DOI: 10.2489/jswc.70.6.340
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing to monitor cover crop adoption in southeastern Pennsylvania

Abstract: Abstract:In the Chesapeake Bay Watershed, winter cereal cover crops are often planted in rotation with summer crops to reduce the loss of nutrients and sediment from agricultural systems. Cover crops can also improve soil health, control weeds and pests, supplement forage needs, and support resilient cropping systems. In southeastern Pennsylvania, cover crops can be successfully established following corn (Zea mays L.) silage harvest and are strongly promoted for use in this niche. They are also planted follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 33 publications
(38 reference statements)
0
36
0
Order By: Relevance
“…Revenue from red clover silage was based on experimental yield and a 5-yr (2010-2014) average price received for alfalfa hay and haylage in six states (Iowa, Illinois, Michigan, New York, Ohio, Pennsylvania; USDA-NASS, 2016), adjusted for moisture. Corn silage was calculated with experimental yield and the Pennsylvania annual average market price (Ishler, 2013). Wheat revenue was calculated by multiplying experimental yield with a 5-yr average price of soft red winter wheat in Pennsylvania from 2008 to 2012 (USDA NASS, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Revenue from red clover silage was based on experimental yield and a 5-yr (2010-2014) average price received for alfalfa hay and haylage in six states (Iowa, Illinois, Michigan, New York, Ohio, Pennsylvania; USDA-NASS, 2016), adjusted for moisture. Corn silage was calculated with experimental yield and the Pennsylvania annual average market price (Ishler, 2013). Wheat revenue was calculated by multiplying experimental yield with a 5-yr average price of soft red winter wheat in Pennsylvania from 2008 to 2012 (USDA NASS, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Cover crops protect soil when a cash crop is not present, reduce potential runoff of soil and nutrients (Clark, 2007), scavenge nutrients not used by the cash crop (Shipley et al, 1992), and green manures can add N to the soil (Dou and Fox, 1994;Liebman et al, 2012). Cover crop adoption is increasing in Pennsylvania (Hively et al, 2015); in some areas cover cropping is subsidized and farmers can receive payments for no-till planting cover crops for the fi rst time, or for planting multi-species cover crop mixtures instead of single-species cover crops (NRCS, 2014;Columbia County Conservation District, 2015).…”
mentioning
confidence: 99%
“…They concluded that intercropping selected legumes with switchgrass might enhance forage yield and quality and provide additional environmental benefits such as reducing fertilizer input and losses of fertilizer to air and groundwater. Hively et al (2015) studied the potential to use remote sensing to monitor cover crop adoption in southeastern Pennsylvania. Over the four-year study, their remote sensing analysis found that farmers are increasing adoption of cover crops following corn harvest.…”
Section: Recent Advances In Cover Crop Use For Improved Soil Quality Andmentioning
confidence: 99%
“…
C over crop use in the mid-Atlantic and other regions of the United States has expanded in recent decades because they are an eff ective tool for reducing erosion and nutrient leaching and because they are a source of recycled N and fi xed N 2 for ecological nutrient management (Drinkwater and Snapp, 2007;Hively et al, 2015). However, it remains a signifi cant challenge to explain the variability and predict the outcome of N cycling processes across a range of cover crop management practices (Ketterings et al, 2015), leaving farmers with few tools to support adaptive N fertility management when using cover crops.
…”
mentioning
confidence: 99%